Apour ti yapour. Na jang na aman. Yeti chu talukpeth. - Raina, Ajay (India; Pakistan, 2011)
A film about lives disrupted by a temporary border that has remained permanent too long. The film maps the distance, people of Kashmir have traveled emotionally and psychologically from the idea of India. Twenty years of violent conflict and the consequent Indian state response may have brought Kashmir to point from where, there is nowhere to go.
Verzio Film Festival Submission
Keywords: Documentary films